2009
DOI: 10.1007/s10548-009-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Visually Evoked Potential Correlates of Static and Dynamic Emotional Face Processing

Abstract: While the neural regions associated with facial identity recognition are considered to be well defined, the neural correlates of non-moving and moving images of facial emotion processing are less clear. This study examined the brain electrical activity changes in 26 participants (14 males M = 21.64, SD = 3.99; 12 females M = 24.42, SD = 4.36), during a passive face viewing task, a scrambled face task and separate emotion and gender face discrimination tasks. The steady state visual evoked potential (SSVEP) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…By considering them together, these results show that static stimuli were processed more strongly at early latencies, whereas natural dynamic stimuli entailed more prolonged processing towards later latencies as expected. (Note that the delta and lower theta PLI response to the static -unlike the natural —FEEs is back to baseline after 700 ms–see Figure A panel (a) of the S1 File) This conclusion agrees with previous studies [22,28] and supports the hypothesis of [19] that prolonged rather than stronger activations could explain the stronger fMRI and PET responses to dynamic FEEs over their static counterparts [1720]. Indeed, PLI and, even more, WP at low frequencies are far from showing stronger activations for natural dynamic than for static stimuli in our results, especially before 800 ms.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…By considering them together, these results show that static stimuli were processed more strongly at early latencies, whereas natural dynamic stimuli entailed more prolonged processing towards later latencies as expected. (Note that the delta and lower theta PLI response to the static -unlike the natural —FEEs is back to baseline after 700 ms–see Figure A panel (a) of the S1 File) This conclusion agrees with previous studies [22,28] and supports the hypothesis of [19] that prolonged rather than stronger activations could explain the stronger fMRI and PET responses to dynamic FEEs over their static counterparts [1720]. Indeed, PLI and, even more, WP at low frequencies are far from showing stronger activations for natural dynamic than for static stimuli in our results, especially before 800 ms.…”
Section: Discussionsupporting
confidence: 92%
“…We anticipated that in the comparison of natural dynamic versus static FEEs, we would find differences mainly in the timing of the perceptual process, in line with the previous findings of [28], as static FEEs depict the “full-blown” expression at the very first video frame, whereas the natural dynamic FEEs develop gradually over time. We therefore expected stimulus-driven activity and task-relevant activations, as captured by PLI and WP respectively, to be higher for static FEEs at early latencies, but more prolonged towards later latencies for natural dynamic FEEs.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…SSVEP has been primarily used to study the brain's sensitivity to low-level properties of visual stimuli (contrast, phase, line orientation, spatial frequencies, motion, e.g., Ales & Norcia, 2009;Braddick, Wattam-Bell, & Atkinson, 1986;Campbell & Maffei, 1970;Heinrich & Bach, 2003;Tyler & Kaitz, 1977;see Regan, 1989), spatial and selective attention (e.g., Andersen, Müller, & Hillyard, 2009;Morgan, Hansen, & Hillyard, 1996), and figure-ground segregation (e.g., Appelbaum, Wade, Pettet, Vildavski, & Norcia, 2008;Appelbaum, Wade, Vildavski, Pettet, & Norcia, 2006). A few recent studies have also used SSVEPs with high-level visual stimuli and showed modulation of the SSVEP amplitude with the affective content of pictures (Keil et al, 2003), object familiarity (Kaspar, Hassler, Martens, Trujillo-Barreto, & Gruber, 2010), as well as to static and dynamic facial expressions (Mayes, Pipingas, Silberstein, & Johnston, 2009). However, to the best of our knowledge, none of these studies or other studies have attempted to use this method to address the issue of how (individual) faces are coded in the human brain.…”
Section: Introductionmentioning
confidence: 99%